The qualitative and quantitative components of input and output of labour force in Sarawak / Yap Yin and Chan Soon Huat - Yin, Yap; Chan, Soon Huat (1992)
In the process of industrial development of a country, the population variables have a close interlinkage with the socio-economic variables. Hence, they must be incorporated into the development plans of a country. However, before making any long-term plan on education, health or provision of basic needs, the vital demographic variables should be considered. For instance, a high rate of population increase will pose a challenging problem of finding productive employment for each new entrant to the labour force. There is a common tendency to overemphasize the so-called 'hardware' of development such as capital, raw materials, land and machineries instead of the 'software' aspects of human resource development especially in developing countries because the process of human resource development is lengthy and its impact can only be realized after a longer period.